The effect of enterprise risk management on the risk and the performance of Spanish listed companies - Luis Otero-González; Pablo Durán Santomil; Aracely Tamayo Herrera (European Research on Management and Business Economics (ERMBE), 2020)
This paper evaluates the effect of Enterprise Risk Management (ERM) on the performance and the financial stability of a sample of non-financial Spanish listed companies. The information about ERM is taken from the annual reports, management reports and annual corporate governance reports disseminated over four years (2012-2015). The data on performance and financial stability have been obtained through the SABI (Iberian Balance Sheet Analysis System) and Morningstar Direct. The results obtained show that the adoption of ERM is not associated with a change in the performance of Spanish companies (measured through the return on equity, return on assets and Tobin's Q) nor does it reduce the probability of bankruptcy. Having a chief risk officer (CRO) can actually reduce performance, although it can improve the degree of financial health measured as the distance to default. Regarding the relationship between the hedging of risks on the profitability and the level of risk, we find evidence of improvement through the hedging of exchange risk.
Keywords: G32; 650; Enterprise Risk Management; ERM; Performance; Risk